GAME PEMBELAJARAN PENDUKUNG MODEL ANCHORED INSTRUCTION UNTUK MENINGKATKAN LOGICAL THINKING SISWA PADA STRUKTUR KONTROL PERCABANGAN - Orva Linnisa, Elliora; Syari'ati Fathimah, Nusuki; Setya Arianti , Andini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Logical thinking is one of the fundamental competencies students need to solve problems systematically, yet studies show that the logical thinking ability of Senior High School (SMA) students remains relatively low, including in learning Informatics on branching control structure material. This study aims to design, implement, and evaluate a learning game that supports the Anchored Instruction model to improve students' logical thinking ability on branching control structure material. The research employed the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and a quantitative approach using a One-Group Pretest-Posttest Design. The sample consisted of 32 eleventh-grade students of SMA Negeri 1 Ngamprah selected through purposive sampling. Data were collected through expert validation sheets, a logical thinking test instrument, and a student response questionnaire, then analyzed using a normality test, the Wilcoxon Signed-Rank Test, and the N-Gain test. The results show that the game design was declared highly feasible by media and material experts with an average score of 90%. The Wilcoxon test revealed a significant difference between pretest and posttest scores (p < 0.001), with an average N-Gain of 0.71, categorized as high. Students also gave a very positive response to the game, with an average percentage of 98.14%. These findings indicate that the learning game, developed to support the problem-presentation stage of Anchored Instruction model, is effective in improving students' logical thinking ability and is well received by students.